Interventional Audiology to Address Hearing Health Care Disparities: Oyendo Bien Pilot Study - Marrone, Nicole; Ingram, Maia; Somoza, Maria; Jacob, Daisey Sánchez; Sanchez, Adriana; Adamovich, Stephanie; Harris, Frances P. (Seminars in Hearing, 2017)
Interventional audiology, specifically community-based outreach, can connect people with the hearing health care system. Community-based participatory research methods were applied in two phases of research to: (1) investigate the needs of families affected by hearing loss in a rural Arizona community on the U.S.–Mexico border; and (2) evaluate an outreach program on hearing health. The needs assessment included interviews with persons with hearing loss and focus groups with family members and the greater community. The needs assessment revealed that despite perceived severity of hearing loss, help-seeking for audiologic care was limited due to barriers, stigma, and low self-efficacy. Results informed development of a community-based pilot study conducted as part of an academic-community partnership between audiology, public health, and community health workers of a federally qualified health center. An outreach program, Oyendo Bien (hearing wellness), a 5-week, Spanish-language health education program for older adults (n = 21) incorporated communication strategies and behavioral change techniques. Postprogram focus groups revealed increased self-efficacy and decreased stigma. After 1 year, 7 of 9 participants with hearing loss contacted for follow-up had sought some form of hearing-related health care. Future research should further investigate interventional audiology approaches to address health disparities.
Keywords: Interventional audiology; community health workers; Hispanic/Latino; community-based participatory research; Health Belief Model